Bariatric Surgery and Cardiovascular Outcomes in Patients With Obesity and Cardiovascular Disease: A Population-Based Retrospective Cohort Study. Issue 15 (13th April 2021) - Doumouras, Aristithes G.; Wong, Jorge A.; Paterson, J. Michael; Lee, Yung; Sivapathasundaram, Branavan; Tarride, Jean-Eric; Thabane, Lehana; Hong, Dennis; Yusuf, Salim; Anvari, Mehran
Abstract : Background: Bariatric surgery has been shown to significantly reduce cardiovascular risk factors. However, whether surgery can reduce major adverse cardiovascular events (MACE), especially in patients with established cardiovascular disease, remains poorly understood. The present study aims to determine the association between bariatric surgery and MACE among patients with cardiovascular disease and severe obesity. Methods: This was a propensity score–matched cohort study using province-wide multiple-linked administrative databases in Ontario, Canada. Patients with previous ischemic heart disease or heart failure who received bariatric surgery were matched on age, sex, heart failure history, and a propensity score to similar controls from a primary care medical record database in a 1:1 ratio. The primary outcome was the incidence of extended MACE (first occurrence of all-cause mortality, myocardial infarction, coronary revascularization, cerebrovascular events, and heart failure hospitalization). Secondary outcome included 3-component MACE (myocardial infarction, ischemic stroke, and all-cause mortality). Outcomes were evaluated through a combination of matching via propensity score and subsequent multivariable adjustment. Results: A total of 2638 patients (n=1319 in each group) were included, with a median follow-up time of 4.6 years. The primary outcome occurred in 11.5% (151/1319) of the surgery group and 19.6% (259/1319) of the controls (adjusted hazard ratio [HR], 0.58 [95% CI, 0.48–0.71]; P <0.001). The association was notable for those with heart failure (HR, 0.44 [95% CI, 0.31–0.62]; P <0.001; absolute risk difference, 19.3% [95% CI, 12.0%–26.7%]) and in those with ischemic heart disease (HR, 0.60 [95% CI, 0.48–0.74]; P <0.001; absolute risk difference, 7.5% [95% CI, 4.7%–10.5%]). Surgery was also associated with a lower incidence of the secondary outcome (HR, 0.66 [95% CI, 0.52–0.84]; P =0.001) and cardiovascular mortality (HR, 0.35 [95% CI, 0.15–0.80]; P =0.001). Conclusions: Bariatric surgery was associated with a lower incidence of MACE in patients with cardiovascular disease and obesity. These findings require confirmation by a large-scale randomized trial. Abstract : Supplemental Digital Content is available in the text.